2022
DOI: 10.1088/1748-9326/ac4a31
|View full text |Cite
|
Sign up to set email alerts
|

Stronger Arctic amplification from ozone-depleting substances than from carbon dioxide

Abstract: Arctic amplification (AA) - the greater warming of the Arctic near-surface temperature relative to its global mean value - is a prominent feature of the climate response to increasing greenhouse gases. Recent work has revealed the importance of ozone-depleting substances (ODS) in contributing to Arctic warming and sea-ice loss. Here, using ensembles of climate model integrations, we expand on that work and directly contrast Arctic warming from ODS to that from carbon dioxide (CO$_2$), over the 1955-2005 period… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 54 publications
6
4
0
Order By: Relevance
“…This offers important new evidence that the large Arctic impact of ODS reported in an earlier study (Polvani et al., 2020), which analyzed the same historical simulations, must be due to strong local feedbacks, notably changes in the lapse rate feedback reported in Liang et al. (2022).…”
Section: Summary and Discussionsupporting
confidence: 55%
See 1 more Smart Citation
“…This offers important new evidence that the large Arctic impact of ODS reported in an earlier study (Polvani et al., 2020), which analyzed the same historical simulations, must be due to strong local feedbacks, notably changes in the lapse rate feedback reported in Liang et al. (2022).…”
Section: Summary and Discussionsupporting
confidence: 55%
“…Third, we have shown that the latitudinal structure of the RF caused by ODS, while broadly similar to those of other GHGs (larger at the equator than at the poles), has an even steeper latitudinal gradient than the RF of CO 2 , thus opposing Arctic Amplification even more strongly. This offers important new evidence that the large Arctic impact of ODS reported in an earlier study (Polvani et al, 2020), which analyzed the same historical simulations, must be due to strong local feedbacks, notably changes in the lapse rate feedback reported in Liang et al (2022).…”
Section: Summary and Discussionsupporting
confidence: 51%
“…Since changes in Arctic temperatures have a direct effect on sea ice loss, Polvani et al [ 59 ] concluded that ODSs contributed half of the forced Arctic sea ice loss in the latter half of the twentieth century. These results were recently confirmed [ 75 ], showing that Arctic warming and sea ice loss from ODSs are slightly more than half (52–59%) of those from CO 2 .…”
Section: Benefits Of the Montreal Protocolsupporting
confidence: 65%
“…Note that the ERF of ODSs opposes Arctic amplification even more than the ERF of CO 2 , making their large contribution to Arctic climate change even more unexpected. This may be due to stronger local feedbacks as suggested by Liang et al (2022).…”
Section: Discussionmentioning
confidence: 92%